Pengaruh Knowledge Management terhadap Kinerja Karyawan - Fata Sabita Ala Dini (UNISBA Press, 2023)
Abstract. Researchers tested the relationship between knowledge management and employee performance. There are two variables analyzed, namely the Knowledge Management variable (X) and the Employee Performance variable (Y). The research was conducted at PT. Ogya Tekno Nusantara with the object of research are IT employees. Questionnaires are used as a data collection technique distributed through Google Forms. The population of the research object is 180 people. The use of probability sampling technique with simple random sampling is used in this study, and using the Slovin formula so that the number of samples is 124 people. Instrument test (validity test and reliability test), classical assumption test (normality test and heteroscedasticity test), and hypothesis testing (simple linear regression analysis, t test and determinant test) with a significance level of 5% or 0.05 were used as analysis techniques. With the output of the regression equation Y= 3.601 + 0.833 and a significance level of 0.03 it can be concluded that Knowledge Management has a positive effect on employee performance. Abstrak. Peneliti menguji kaitan antara knowledge management terhadap kinerja karyawan. Terdapat dua variabel yang dianalisis yaitu variabel Knowledge Management (X) dan variable Kinerja Karyawan (Y). Penelitian dilakukan di PT. Ogya Tekno Nusantara dengan objek penelitian adalah karyawan IT. Kuesioner digunakan sebagai teknik pengumpulan data yang disebar melalui Google Form. Populasi pada objek penelitian berjumlah 180 orang. Penggunaan teknik probability sampling dengan simple random sampling digunakan pada penelitian ini, serta menggunakan rumus slovin sehingga didapat jumlah sampel sebanyak 124 orang. Uji instrument (uji validitas dan uji reliabilitas), Uji asumsi klasik (uji normalitas dan uji heterokedastisitas), serta uji hipotesis (analisa regresi linier sederhana, uji t dan uji determinan) dengan tingkat signifikansinya adalah 5% atau 0.05 digunakan sebagai teknik analisis. Dengan hasil output persamaan regresi Y= 3.601 + 0.833 serta tingkat signifikansi 0.03 maka dapat ditarik kesimpulan bahwa Knowledge Management berpengaruh positif terhadap Kinerja Karyawan.